"Seeking for a Better Place": American Dream in Kuntowijoyo's Impian Amerika - Tri Pramesti; Adeline Grace Marianne Litaay; Dita Dwi Ayunanda; Clara Febrianna (Tell : Teaching of English Language and Literature Journal, 2020)
Impian Amerika by Kuntowijoyo tells stories of Indonesian immigrants who came to New York City with different reasons and backgrounds. They settle, move, go to school, work, and live in the United States-especially around the New York City area. There are Javanese, Achenese, Batak, Manado, Sundanese, Minangs, Makassarese, and others. There are various reasons why they decide to settle in this city, but the majority is for advancement, prosperity, and freedom. Some continue their education or study in the United States because of the more advanced education system. Some chose to work as long as they can go and settle in United States because the country is more prosperous than Indonesia. Other chose the United States because they want to be free and adventurous. In addition, this novel also presents ethic problems between Indonesians and other citizen due to multidimensional relationships and the daily lives of Indonesians. The purpose of this study is to scrutinize how the American Dream is understood by immigrants, especially immigrants from Indonesia. This work used qualitative research method and data was collected from Kuntowijoyo's Impian Amerika. The data was analyzed qualitatively using Marxist literary approach. The result of the study shows that Kuntowijoyo's Impian Americas hows how material success is not automatically followed by spiritual success. As an ethos, the American Dream is able to offer people to come to America to migrate, work and live there forever and promise that anyone can succeed by working hard regardless of family and social background but American dream can also mislead someone or immigrant if he does not have a strong religious and moral basis.